Solar Thermal Energy: Polydopamine Nanoparticle Doped Nanofluid for Solar Thermal Energy Collector Efficiency Increase (Adv. Sustainable Syst. 1/2020). (17th January 2020) - Hauser, Daniel; Steinmetz, Lukas; Balog, Sandor; Taladriz‐Blanco, Patricia; Septiadi, Dedy; Wilts, Bodo D.; Petri‐Fink, Alke; Rothen‐Rutishauser, Barbara
Abstract : In article number 1900101, Barbara Rothen‐Rutishauser and co‐workers dope solar fluids used in solar thermal energy with polydopamine/bovine serum albumin nanoparticles. The solar fluids produced are circulated through a 3D printed collector, whereby the addition of these nanoparticles results in an efficiency temperature increase of the solar fluid compared to soot particle and silver nanoparticle doped fluids.